2006
DOI: 10.1103/physrevb.74.115318
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-weight dependence of interchain polaron delocalization and exciton bandwidth in high-mobility conjugated polymers

Abstract: Interchain interactions have a profound effect on the optical as well as charge transport properties of conjugated polymer thin films. In contrast to oligomeric model systems in solution-deposited polymer thin films the study of such effects is complicated by the complex microstructure. We present here a detailed study of interchain interaction effects on both charged polarons as well as neutral excitons in highly crystalline, high-mobility poly-3-hexylthiophene ͑P3HT͒ as a function of molecular weight. We fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
342
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 293 publications
(367 citation statements)
references
References 59 publications
(69 reference statements)
23
342
1
1
Order By: Relevance
“…31 A similar signal also appeared as a shoulder at 0.6 eV in CMS measurements within the IR region but was not discussed. 35 As a result, we exclude the existence of 2D polarons in our F4TCNQ doped P3HT and propose that polarons in this system prefer to localize on single P3HT chains. Therefore, charge carriers in F4TCNQ doped P3HT films can only be polarons, or a combination of polarons and bipolarons.…”
Section: Doping In Thin Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…31 A similar signal also appeared as a shoulder at 0.6 eV in CMS measurements within the IR region but was not discussed. 35 As a result, we exclude the existence of 2D polarons in our F4TCNQ doped P3HT and propose that polarons in this system prefer to localize on single P3HT chains. Therefore, charge carriers in F4TCNQ doped P3HT films can only be polarons, or a combination of polarons and bipolarons.…”
Section: Doping In Thin Filmsmentioning
confidence: 99%
“…In the IR region, absorption peaks with energy lower than 0.2 eV were observed in both cases in regio-regular P3HT. 31,35 These peaks were identified as delocalized or 2D polarons, with energies much smaller than our IR absorption. On the other hand, absorption around 0.5 eV observed in PIA of regio-random P3HT was assigned to the P1 transition (Fig.…”
Section: Doping In Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron tomography results of Loos discussed above also observed a preferential segregation of P3HT at the bottom interface (in this case PEDOT:PSS). 5 The authors noted that some pre-aggregation in solution prior to coating may also account for this. More recently using a combination of NEXAFS, XRD, UV-Vis and XRD, Dastoor and co-workers have suggested that a three phase morphology, with thin P3HT rich interfacial layer at both the bottom and top interfaces, sandwiching a blended phase.…”
Section: Blend Compositionmentioning
confidence: 99%
“…[13] Indeed, the strength of the shoulder at $600 nm has been related to the degree of interchain order in regioregular P3HT and may be used as a probe of film microstructure. [14] P3HT films also exhibit a larger extinction coefficient than films of F8TBT, with the absorption spectra in Figure 1 normalized to film thickness. Comparing the photoluminescence (PL) of these two materials, F8TBT is more luminescent, with a photoluminescence quantum efficiency (PLQE) of 35% compared to only 4% for P3HT.…”
Section: Full Papermentioning
confidence: 99%